(untitled) (Journal of Human Sciences, 2021)
The The Karamanions ruled the governorate of Tripoli for a period of 124 years, which was full of family struggles in order to gain power. On the other hand, revolutions were relentless to get rid of the oppression of rulers, and the main factor that helped this family to reach power was the political and economic decline of the Ottoman Empire, which led Due to the decline of its political and military capabilities, and thus it was no longer able to influence the political events in the Ayala, it found in front of it only acceptance of the fait accompli, which is recognition of the Karamanli rule in exchange for loyalty to the state and the Sultan, in addition to all these matters contributed to the arrival of this family to power, and thus the Ottoman rule ended Direct Scrolling. The rulers of this family tried to establish their rule almost independently of the central authority, and to regulate their financial, judicial and military affairs, relying on the ideological social class that owes their allegiance to them in establishing the foundations of power through its formation of the main force in the army. The study Problem: This research represents an analytical study that aims to focus on the main and important aspects of the political role of the Karamanli family in the province of western Tripoli. Which necessitated his research and discussion to be clear to the eye by answering many questions related to this topic, and thus leads the researcher to answer them, and thus the problem of this study appears about the following main question: What is the political role of the Karamanli family in the province of western Tripoli, with Fezzan and the regions beyond the desert during the reign of Yusuf Pasha in the period from 1795/1832 AD Thus, this study attempted to answer several questions, including: 1- How was the relationship of the state of Tripoli with Fezzan in the era of the Karamanli family during the rule of Yusuf Pasha? 2- How was the relationship of the state of Tripoli with the regions beyond the desert during the reign of the Karamanli family during the rule of Yusuf Pasha? Study Value: This study deals with the political relations of the Karamanli family, with Fezzan and the regions beyond the Sahara during the reign of Yusuf Pasha ((1795 AD 1832 AD)). That family that ruled the governorate of western Tripoli, or what is called Libya at the present time As well as studying this historical period of great importance because it provides us with a clear picture of the history of the political relations of the Karamanli family with Fezzan and the regions beyond the desert during the reign of Yusuf Pasha in that historical period, which we can define its beginning in the year 1795 AD and also its end in the year 1832 AD, which is the year Which ended the rule of Yusef Pasha. Results: It was a result of the political relations of the Karamanli family with the Fezzan and the regions beyond the Sahara Subjugation of the areas of the south and the right to direct administration in the province of western Tripoli. Ghadames was subjugated in 1810 AD, which crossed the trade gateway to western Sudan, and the meeting place for commercial caravans coming from Tunisia and Algeria. Yusef Pasha was subjected to Fezzan after Ghadames, where his intervention came in the year 1811 AD. 1812 AD. 4. The fall of the state of the children of Muhammad at the hands of Muhammad al-Makni, who attacked the last sultans of the state of the children of Muhammad called Muhammad al-Nasser, who took over Fezzan in 1804 AD.